2008
DOI: 10.2478/v10063-009-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of relative humidity on the wettability of silicon wafer surfaces

Abstract: Investigation of wetting properties of the original silicon wafers and modified by oxidation was carried out by contact angles measurements of water at varying relative humidity (RH) of the atmosphere present in the measuring chamber. At three selected humidities (10, 30 and 50%) contact angles of diiodomethane and formamide were also determined for the original silicon wafer only. The topography of the tested surfaces was determined with the help of atomic force microscopy (AFM). Using the measured contact an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…The Lifshitz-van der Waals LW S component of the powdered quartz determined by the I-D method is 42.8 mJ/m 2 and corresponds well to the mean value of 41.1 mJ/m 2 obtained by the thin-layer wicking method from the penetration rates of 12 n-alkanes [29]. Moreover, it correlates well with the values of apolar interactions of silica materials evaluated by other experimental methods [30,31]. The apolar interactions of the DPPC monolayer are close to that of bare quartz; however the electron-donor interactions are significantly higher, while the electron-acceptor ones are lower than those of bare quartz.…”
Section: Surface Free Energy and Its Components Of Modified Quartz Posupporting
confidence: 79%
“…The Lifshitz-van der Waals LW S component of the powdered quartz determined by the I-D method is 42.8 mJ/m 2 and corresponds well to the mean value of 41.1 mJ/m 2 obtained by the thin-layer wicking method from the penetration rates of 12 n-alkanes [29]. Moreover, it correlates well with the values of apolar interactions of silica materials evaluated by other experimental methods [30,31]. The apolar interactions of the DPPC monolayer are close to that of bare quartz; however the electron-donor interactions are significantly higher, while the electron-acceptor ones are lower than those of bare quartz.…”
Section: Surface Free Energy and Its Components Of Modified Quartz Posupporting
confidence: 79%
“…Nine datasets among thirty droplets tested in this study are shown to have TI and RI simultaneously in the given field of views. The initial contact angles of water droplets on cleaned silicon wafers were 20-50 degrees, 25 which are typical for silicon wafer with angle hysteresis (∼ 10 • ) 12,25 and under laboratory humidity.…”
Section: Copyright 2011 Author(s) This Article Is Distributed Under mentioning
confidence: 98%
“…The advancing contact angle (Θ a ) and receding one (Θ r ) of each of three different test liquids were determined on the surfaces of the luting cements and dentin by the dynamic sessile drop method at room temperature using a contact angle measurement apparatus (OCA 15 plus, DataPhysics Instrument GmbH, Filderstadt, Germany). Although solid surface energy parameters calculated from the LWAB approach are theoretically similar irrespective of the probe liquid used, [25] Combe et al [26] clearly showed that the choice of liquid triplets remains critical even in applying the LWAB method. In this study, water (W: γ: 72.8; γ LW : 21.8; γ + : 25.5; γ À : 25.5), glycerol (G: γ: 64; γ LW : 34; γ + : 3.92; γ À : 57.4), and methylene iodide (MI: γ: 50.8; γ LW : 50.8) were used as the test liquids (all in mJ m À2 ).…”
Section: Surface Energy Parametersmentioning
confidence: 99%
“…The receding contact angle was then measured after sucking 2 μL from the droplet into the syringe (Figure 1). [25,29] In the LWAB approach, only the advancing contact angles were employed. [25] If the solid shows contact angle hysteresis (CAH, the difference between advancing and receding contact angles), the CAH phenomenon can be utilized to characterize the surface.…”
Section: Surface Energy Parametersmentioning
confidence: 99%
See 1 more Smart Citation